Laporan Kasus: Penatalaksanaan Gingivitis Gravidarum pada Ibu Hamil di RSGM Universitas Jenderal Soedirman - Rinawati Satrio; Puspaningdyah Pramudyanaswari (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2022)
Gingivitis gravidarum is a pathological process that occurs during pregnancy on the supporting tissues of the teeth where there is gingival enlargement which causes discomfort due to increased estrogen and progesterone hormones. The etiology of gingival gravidarum originates from plaque in the oral cavity triggered by systemic factors such as hormones in pregnancy that cause inflammation and enlargement of the gingiva. The purpose of this case report is to find out about the management of gingivitis gravidarum that occurs in pregnant women. A 23-year-old female patient came with complaints of swelling of the anterior upper and lower gingival regions. These complaints have increased since entering the fourth week of pregnancy and spontaneous bleeding gums when brushing teeth. Intraoral examination revealed gingival swelling in the maxillary anterior region and mandibular interdental area extending to the gingival margin. Bleeding on probing showed positive results, while the O'leary score showed 28.28% and OHI-s showed 2.9 results. The treatment that will be carried out is USS scaling and patient education to always maintain oral hygiene. Gingivitis gravidarum often occurs in the area of the interdental gingival margin, which looks red and swollen. Periodontal treatment in pregnant women is more focused on controlling periodontal disease and eliminating the causative factors and treatments such as scaling can be carried out, while periodontal surgical treatment for pregnant women such as gingivectomy should be postponed until the delivery period is complete.